2017
DOI: 10.1242/jeb.144113
|View full text |Cite
|
Sign up to set email alerts
|

Acid–base physiology, neurobiology and behaviour in relation to CO2-induced ocean acidification

Abstract: Experimental exposure to ocean and freshwater acidification affects the behaviour of multiple aquatic organisms in laboratory tests. One proposed cause involves an imbalance in plasma chloride and bicarbonate ion concentrations as a result of acid-base regulation, causing the reversal of ionic fluxes through GABA A receptors, which leads to altered neuronal function. This model is exclusively based on differential effects of the GABA A receptor antagonist gabazine on control animals and those exposed to elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 117 publications
5
75
0
Order By: Relevance
“…Our EEG recordings support this hypothesis, as elevated CO 2 exposures increased the amplitude, and tended to increase the duration of odorant‐induced responses within specific regions of the olfactory bulb. This CO 2 ‐induced increase in excitatory signaling is consistent with the hypothesis that disruption of neuronal signaling in marine fish is associated with disruption of inhibitory GABA signaling (Nilsson et al, ; Tresguerres & Hamilton, ). Specific odorant‐generated signals in the olfactory bulb guide odorant perception and downstream behaviors.…”
Section: Discussionsupporting
confidence: 87%
“…Our EEG recordings support this hypothesis, as elevated CO 2 exposures increased the amplitude, and tended to increase the duration of odorant‐induced responses within specific regions of the olfactory bulb. This CO 2 ‐induced increase in excitatory signaling is consistent with the hypothesis that disruption of neuronal signaling in marine fish is associated with disruption of inhibitory GABA signaling (Nilsson et al, ; Tresguerres & Hamilton, ). Specific odorant‐generated signals in the olfactory bulb guide odorant perception and downstream behaviors.…”
Section: Discussionsupporting
confidence: 87%
“…If cognitive function is affected, causing fish to engage in risky behaviors, predation rates may become high (Munday et al, 2010). The only mechanism proposed to date is based on the altered function of gamma-aminobutyric acid type A (GABA-A) receptors found in the vertebrate brain (Tresguerres and Hamilton, 2017). A study by Nilsson et al (2012) found that exposure to gabazine (a GABA-A receptor antagonist) restored the loss of olfactory discrimination in orange clownfish (A. percula), and reversed the loss of lateralisation behavior in damselfish (Neopomacentrus azysron), that were reared in high CO 2 conditions.…”
Section: Disruption Of Learning Processes: Olfactory and Visual Cuesmentioning
confidence: 99%
“…3 ) and releasing chloride (Cl − ) ions; regulatory changes that lead to a reversal in GABA A receptor function (inhibition to excitation) and impairment of behavioral processes (Nilsson et al, 2012;Tresguerres and Hamilton, 2017). Altered function of GABA A receptors, with corresponding effects on fish behavior, has since been reported in a number of studies on both marine and freshwater organisms (reviewed by Tresguerres and Hamilton, 2017) and is caused by a change in intracellular and extracellular HCO − 3 levels in the brain and blood plasma (Heuer et al, 2016). However, beyond this, little is known about distribution and subunit composition of GABA A receptors in fish, or the function and regulation of other neural pathways involved in HCO − 3 and Cl − transport (Heuer et al, 2016).…”
Section: Elevated Co 2 Aquatic Contaminants and Gaba A Receptor Fumentioning
confidence: 99%
“…Changes in environmental conditions can cause stress through molecular damage that requires energy to repair, as in the damage causing proteotoxic effects (e.g., Kültz, 2005). Environmental changes can also increase the maintenance requirements for homeostatic processes by disrupting or shifting acid-base balances and ionic gradients (Pörtner, 2008;Calosi et al, 2013;Tresguerres and Hamilton, 2017). Increased maintenance of homeostatic processes and up-regulation of stress response pathways could prevent mortality of coral larvae under stressful environmental conditions, though the energetic costs of stress response may slow developmental timing, reduce growth, and impair competency to settle (Albright et al, 2010;Albright and Langdon, 2011;Timmins-Schiffman et al, 2013;Ko et al, 2014).…”
Section: Introductionmentioning
confidence: 99%